2020
DOI: 10.1039/c9cp06472a
|View full text |Cite
|
Sign up to set email alerts
|

First-principles prediction of a two-dimensional vanadium carbide (MXene) as the anode for lithium ion batteries

Abstract: MXene V2C structure provides a specific theoretical capacity as high as 472 mA h g−1 at the Li2V2C stoichiometry and extremely fast diffusion with an energy barrier less than 0.1 eV. These intriguing findings are robust against intrinsic structural defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…[199] The energy barriers for the second lithium ion diffusing along H c -B-H c and H c -H v -H c on the V 2 C surface with an occupied V V site were calculated to be 0.032 and 0.02 eV, as shown in Figure 18 (d) and (e). [199] Compared with defect-free V 2 C, the one with vanadium vacancies displayed a stronger binding ability to lithium ions (evidenced by a 30 % increase in binding energy) and slightly better diffusion kinetics (illustrated by a reduction in diffusion energy barrier by 0.002 eV). [167,199] Oppositely, Wu et al suggested that the presence of transition metal vacancy in Mo 2 C might have a minor negative influence on the rate performance of lithium-ion batteries.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
See 4 more Smart Citations
“…[199] The energy barriers for the second lithium ion diffusing along H c -B-H c and H c -H v -H c on the V 2 C surface with an occupied V V site were calculated to be 0.032 and 0.02 eV, as shown in Figure 18 (d) and (e). [199] Compared with defect-free V 2 C, the one with vanadium vacancies displayed a stronger binding ability to lithium ions (evidenced by a 30 % increase in binding energy) and slightly better diffusion kinetics (illustrated by a reduction in diffusion energy barrier by 0.002 eV). [167,199] Oppositely, Wu et al suggested that the presence of transition metal vacancy in Mo 2 C might have a minor negative influence on the rate performance of lithium-ion batteries.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…Thus, it is believed that the incorporation of vacancies might modify the charge storage capability of 2D nanomaterials, such as MXenes. [198] Defect engineering of MXenes has been studied theoretically, including the influence of termination vacancies (À Cl deficiency on the surface of Ti 3 C 2 Cl 2 ), [196] carbon vacancies (in V 2 C) [199] as well as transition metal vacancies (in Mo 2 C) [200] on the electrical properties of the corresponding MXenes. Experimentally, defective MXenes could be prepared by selectively etching A layers and metal elements in quaternary solid-solution MAX phase (such as (Nb 2/3 Sc 1/3 ) 2 AlC) or ordered quaternary MAX phases ((Mo 2/3 Sc 1/3 ) 2 AlC).…”
Section: Vacancy Engineeringmentioning
confidence: 99%
See 3 more Smart Citations